2016
DOI: 10.4103/1463-1741.178480
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of staff and family perceptions of causes of noise pollution in the Pediatric Intensive Care Unit and suggested intervention strategies

Abstract: Noise and excessive, unwanted sound in the Pediatric Intensive Care Unit (PICU) is common and has a major impact on patients’ sleep and recovery. Previous research has focused mostly on absolute noise levels or included only staff as respondents to acknowledge the causes of noise and to plan for its reduction. Thus far, the suggested interventions have not ameliorated noise, and it continues to serve as a barrier to recovery. In addition to surveying PICU providers through internet-based software, patients’ fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These studies support our findings, and revealthat ambient noise in the ICU exceeds WHO guidelines 1,20. Though it has been shown that levels significantly exceeded the recommended standards, values were 40–60 dB(A) with no significant day/night-shift variation 8,21,22…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These studies support our findings, and revealthat ambient noise in the ICU exceeds WHO guidelines 1,20. Though it has been shown that levels significantly exceeded the recommended standards, values were 40–60 dB(A) with no significant day/night-shift variation 8,21,22…”
Section: Discussionmentioning
confidence: 96%
“…Nonetheless, it is considered a preventable injury when produced by occupational noise 7. Recent Swedish studies found that noise levels in ICUs remain high and that only 10% of ICU staff decrease volumes on alarms, monitors and ventilators during the day8…”
Section: Introductionmentioning
confidence: 99%
“…54 Although equipment alarms likely contribute significantly to noise pollution, this was not an easily modifiable source in our PICU. 55 Therefore, we focused on other easy-to-perform tasks that could reduce noise pollution impacting sleep quality. Examples of tasks incorporated in the Evening BED to emphasize reduction of noise pollution were speaking with a quiet voice, grouping vital sign and nursing care activities, closing patient room doors, setting the staff pagers and phones to vibration mode, and turning the television off at night.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that the subjective annoyance of the sound increases upon raising the sound level. However, at low sound levels, other factors determine whether annoyance occurs (2,3). Noise exerts psychological and physiological effects on humans (4).…”
Section: Introductionmentioning
confidence: 99%